Faktor-Faktor yang Berhubungan dengan Kejadian Abortus di Rumah Sakit Muhammadiyah Palembang: Penelitian - Puspitasari, Selly; Murbiah, Murbiah; Yuniza, Yuniza (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Pregnancy is a process that begins with the meeting of sperm cells and ovum in the ovary, called conception, until it develops into a zygote, attaches to the uterine wall, forms a placenta, and grows into a fetus until it is finally born. The normal pregnancy period lasts for 280 days (40 weeks or 9 months 7 days), calculated from the first day of the last menstruation. Abortion is one of the reproductive health problems in women of childbearing age that can cause physical and psychological problems. Factors that cause abortion include maternal age, parity (pregnancy spacing), gestational age, history of previous abortions, occupation, and maternal education level. Objective: To determine the relationship between factors and the incidence of abortion at the Muhammadiyah Hospital in Palembang. Quantitative research with a cross-sectional design with a population of 111 people with a sample of 53 respondents using a questionnaire of 9 questions. Statistical tests using the Chi-Square test. The results of the study obtained a P-value of maternal age 0.003, parity 0.003, history of abortion 0.004, gestational age 0.004, employment 0.001, education level 0.002. The six factors above the p-value <0.05, meaning that there is a relationship between maternal age, parity, history of abortion, gestational age, employment, and education level with the incidence of abortion at the Muhammadiyah Hospital in Palembang.